A Literature Review: Succession Planning in Family Businesses - Sasminto, Heri; Wening, Nur; Sujoko, Sujoko (Sharia Economics Department Universitas KH. Abdul Chalim, Mojokerto, 2024)
This article presents succession planning that can affect family businesses that are owned and managed by families that have been analyzed and tested regarding family businesses being able to develop and survive to the next generation and identify the main research topics, namely succession planning, and method approaches to understanding succession planning in family businesses. This study uses the SRL (Systematic Literature Review) research type, the results of several studies agree that succession planning must be prepared early. While other studies agree that succession planning is carried out when the prospective generation is mature and has the knowledge to manage and lead a family business, it does not mean that potential successors are not taught about their family business, it's just that their duties are not burdened on potential successors.